2022
DOI: 10.4269/ajtmh.21-0643
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years of Universal Testing: How the Rapid Diagnostic Test Became a Game Changer for Malaria Case Management and Improved Disease Reporting

Abstract: In 2010, the World Health Organization changed its guidance on malaria case management, recommending parasitological confirmation of all suspected cases before treatment with an antimalarial. This recommendation was in large part as a result of the availability of quality assured malaria rapid diagnostic tests (RDTs) that made it possible for malaria diagnosis to be performed by laboratory staff in all health facilities irrespective of the facility’s place in the tiered health system. Community health workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…The rate of mRDT testing for suspected malaria cases in SSA rose from 36% in 2010 to 84% in 2018. 34 However, an increasing number of mRDT manufacturers has resulted in variability in testing performance. Meta-analysis conducted in 2022 concluded that conventional mRDTs might be only 42% sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of mRDT testing for suspected malaria cases in SSA rose from 36% in 2010 to 84% in 2018. 34 However, an increasing number of mRDT manufacturers has resulted in variability in testing performance. Meta-analysis conducted in 2022 concluded that conventional mRDTs might be only 42% sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…In another study from Yeung et al ( 42 ), this ultrasensitive RDT had a SEN of between 53.8% and 60% compared to qPCR in a low-transmission setting targeting asymptomatic P. falciparum infections. Although deletions in Pf HRP2/3 have been widely reported, their prevalence in sub-Saharan Africa remains low ( 43 ). We also performed a Pf HRP2 ELISA because it is an indicator of total parasite biomass, and its performance reflects the current diagnostic tools available in this region.…”
Section: Discussionmentioning
confidence: 99%
“…With the inclusion of the WHO Methods Manual for product testing of malaria rapid diagnostic tests [51], the quality and trust in RDTs improved. Aidoo et al [52] reported an increase in the RDT testing rate for malaria from 36 (2010) to 84% (2018) in sub-Saharan Africa, with an increase from 100 million supplied malaria RDTs in 2010 to 348 million in 2019. RDTs have also allowed for increased availability of testing for malaria in remote and rural areas [52].…”
Section: Malaria Rapid Diagnostic Testingmentioning
confidence: 99%